Context modelling in process of developing employment solutions - Zavushchak, I.; Burov, Ye.; Pasichnyk, V. (My University, 2018)
The intelligent decision making requires the consideration of current contextual information. The article is devoted to construction of formal models for the presentation and usage of contextual information for decision-making in the field of employment. The paper analyses existing approaches to the definition of the concept of context at the conceptual level. The results of comparison of formal context models taking into consideration the requirements for employment business processes are presented. The ontological approach is selected as a basis for contextual models specification. The paper presents the formal representation of the context models for business operations of the employment sector. The model of contextual graphs for the solution of the problem of employment business operations context refinement was developed.
Keywords: models; context; knowledge; contextual model; employment